Basal Ganglia and MRI in Tourette's Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
Volumetric MRI changes in the basal ganglia of 37 children with Tourette's syndrome (TS), with and without ADHD, compared to 18 controls are reported from Johns Hopkins University School of Medicine, Baltimore, MD.